A dispersive liquid–liquid microextraction and chiral separation of carvedilol in human plasma using capillary electrophoresis. (May 2015) - Hamidi, Samin; Soltani, Somaieh; Jouyban, Abolghasem
Background: Development of simple, rapid and precise analysis of chiral drugs in biological samples is an important issue. Dispersive liquid–liquid microextraction in combination with CE using field amplified sample injection has been of interest because of its capability to analyze trace amount of drugs.Methods: Dispersive liquid–liquid microextraction-CE-field amplified sample injection was employed for chiral separation of carvedilol in human plasma using UV-DAD detector and the developed method has been validated according to US FDA method validation guideline for bioanalysis.Results: The method was linear over a concentration range of 12.5–100 ng/ml for each carvedilol enantiomer (R 2 = 0.998) and the mean recoveries ranged from 91 to 107%.Conclusion: The method was adapted for sensitive, selective and rapid determination of carvedilol enantiomers in human plasma samples.